KERAHASIAAN REKAM MEDIS DI RUMAH SAKIT AVECIENA MEDIKA MARTAPURA - Nina Rahmadiliyani; Faizal Faizal (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
Medical records are managed by procedures and standards and policies of the organization. Information on identity, diagnosis, history of disease, history of examination, and patient medical history are kept confidential by doctors, dentists, health workers, management officers and leaders of health care facilities. This study aims to provide an overview of confidentiality and medical record request process at the Medical Record Unit of Aveciena Medika Hospital. The research method used is descriptive qualitative method. The data collection process was done by observation and interview to the officer of Medical Record Work Unit for 3 people. Result: the implementation of medical record confidentiality is an unwritten agreement, by using oath to medical recorder, doctor, dentist in stored medical record file. In the request of medical records relating to legal aspects, institutions or institutions of the insurer, and the interests of the patient, medical records can not be borrowed or taken out but are allowed to borrow copies of copies of resumes provided that there is a cover letter from the court or the insurer and make written permission. Conclusion. Medical Record Work Unit does not yet have a comprehensive medical records confidentiality policy and is still implemented in small units in terms of filling room permit. Requests for medical information should be preceded by making written permission addressed to the leader of the health service facility.